1977
DOI: 10.1002/jmv.1890010205
|View full text |Cite
|
Sign up to set email alerts
|

The proteins of hepatitis B dane particle cores

Abstract: Although several studies have been done to analyze the peptides of purified 22-nm HbsAg particles, no information has been published about the peptides of the core of the Dane particle which bears the other hepatitis B viral antigen. HbcAg. Dane particles and Dane particle cores (produced by NP-40 treatment of Dane particles) were purified by equilibrium centrifugation in CsCl density gradients. Two populations of Dane particles were observed at densities 1.27 and 1.24 g/ml, respectively. The higher buoyant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 25 publications
4
35
0
Order By: Relevance
“…In addition, it has been previously reported that unenveloped core particles migrate to the same density. 29 The high concentrations of HBsAg contained in fractions nine to twelve most likely represent HBsAg filaments and spheres which have been reported to migrate to these densities. 31 …”
Section: Gradient Analysis Of Extracellular Hbv Particles Produced Bymentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, it has been previously reported that unenveloped core particles migrate to the same density. 29 The high concentrations of HBsAg contained in fractions nine to twelve most likely represent HBsAg filaments and spheres which have been reported to migrate to these densities. 31 …”
Section: Gradient Analysis Of Extracellular Hbv Particles Produced Bymentioning
confidence: 93%
“…Results from HBsAg and DNA analyses of the gradient suggest that the DS and RC HBV DNA in fractions eight and nine are derived from enveloped Dane particles because HBsAg is present in these fractions and because HBV DNA and HBsAg comigrate at a density which has previously been reported for Dane particles. 29,30 DNA detected in fractions four and five most likely indicates the presence of extracellular core particles lacking envelopes because these fractions are devoid of HBsAg. In addition, it has been previously reported that unenveloped core particles migrate to the same density.…”
Section: Gradient Analysis Of Extracellular Hbv Particles Produced Bymentioning
confidence: 99%
“…The 2.2.15 cell line, a well-known HBV-transfected HepG2 cell line, was maintained under conditions described previously (33). After passage through a 40-m-pore-size filter, HBV-positive 2.2.15 cell line culture medium with a high HBV titer (10 9 copies/ml) was subjected to CsCl gradient analysis (16,36). One milliliter of sample was loaded on top of 9 ml of a 20% (wt/wt) CsCl (Boehringer Mannheim, Mannheim, Germany) in phosphate-buffered saline solution.…”
mentioning
confidence: 99%
“…wt. components are often seen in liver-derived core preparations (Hruska & Robinson, 1977;Fields et al, 1977). Neurath et al (1978) found that core antigen prepared c, R. HOWARD from sera with or without HBeAg was heterogeneous with respect to isoelectric point; core antigen from HBeAg-positive serum produced two fractions separated by centrifugation in contrast to only one from HBeAg-negative serum.…”
Section: Expression Of Gene Sequencesmentioning
confidence: 99%